BIMBINGAN KELOMPOK MENGGUNAKAN TEKNIK CINEMA THERAPY UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK DI KELAS X SMK PGRI 3 CIMAHI - Nur Afifah, Nandytha Meidiana; Supriatna, Ecep; Fitri Annisa, Dona (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
The background of this study is the low motivation to learn students. The purpose of this studywas to determine the increase in student motivation after group guidance services using cinematherapy techniques in class X students at SMK 3 PGRI Cimahi. Themethod in this study usesthe mix method method with the design of The Explaratory Sequential Design. The selectedpopulation was 37 students and then there were 8 students sampled. The sample was selected using purposive sampling, where the researcher took a sample by determining the characteristics, namely class X students who experienced and felt low motivation, students whoscored on the pre-test were in the low category. From the results of the pre-test scores, therewere 5 students in the high category, 24 students in the medium category and 8 students in thelow category. The results showed that group guidance services using cinema therapy techniques were able to increase learning motivation, due to an increase between pre-test results with an average of 179.88 andpost-test results with an average of 210.75 there was an increase score of 30.88. This means that Ha is accepted and H0 is rejected with paired sample t-test results of 0.000 < 0.05.